Peningkatan Nilai Tambah Tanaman Obat pada Pekarangan Rumah Ibu-ibu PKK (Pemberdayaan Kesejahteraan Keluarga) Kecamatan Pasirwangi, Kabupaten Garut - Siti Sadiah; Sandra Arifin Aziz; Auliya Ilmiawati; Taopik Ridwan (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Polyscias scutellaria can be planted as hedge plants at home. This plant has many advantages, one of which is a hair tonic that already has a patent number. To be used on an industrial scale, it is necessary to provide raw materials on a large scale, which can be done by planting in certain regions. The objective is that the empowerment of the PKK in Pasirwangi District, Garut will make the Pasirwangi sub-district one of the centers for producing P. scutellaria leaf raw materials. The activities carried out include educating on the use of medicinal plants, especially P. scutellaria and ginger, practicing training on planting techniques, cultivating them, and giving P. scutellaria cuttings and post-harvest processing techniques. This activity is an activity of the IPB Lecturer Homecoming Program in 2022 which is carried out in several stages. Evaluation and monitoring of cultivation executed two months after training. The evaluation results showed that there was an increase in knowledge related to the cultivation of P. scutellaria and participants cultivated P. scutellaria in their garden after the training was more than 90%. All of the participant’s responses to the training carried out stated that it was very useful and hoped that the activities would be sustainable.